Unraveling the Regulatory Mechanism of Color Diversity in Camellia japonica Petals by Integrative Transcriptome and Metabolome Analysis - Fu, Mingyue; Yang, Xu; Zheng, Jiarui; Wang, Ling; Yang, Xiaoyan; Tu, Yi; Ye, Jiabao; Zhang, Weiwei; Liao, Yongling; Cheng, Shuiyuan; Xu, Feng (Frontiers in Plant Science, 2021)
Camellia japonica petals are colorful, rich in anthocyanins, and possess important ornamental, edible, and medicinal value. However, the regulatory mechanism of anthocyanin accumulation in C. japonica is still unclear. In this study, an integrative analysis of the metabolome and transcriptome was conducted in five C. japonica cultivars with different petal colors. Overall, a total of 187 flavonoids were identified (including 25 anthocyanins), and 11 anthocyanins were markedly differentially accumulated among these petals, contributing to the different petal colors in C. japonica. Moreover, cyanidin-3-O-(6''-O-malonyl) glucoside was confirmed as the main contributor to the red petal phenotype, while cyanidin-3-O-rutinoside, peonidin-3-O-glucoside, cyanidin-3-O-glucoside, and pelargonidin-3-O-glucoside were responsible for the deep coloration of the C. japonica petals. Furthermore, total of 12,531 differentially expressed genes (DEGs) and overlapping DEGs (634 DEGs) were identified by RNA sequencing, and the correlation between the expression level of the DEGs and the anthocyanin content was explored. The candidate genes regulating anthocyanin accumulation in the C. japonica petals were identified, and included 37 structural genes (especially CjANS and Cj4CL), 18 key differentially expressed transcription factors (such as GATA, MYB, bHLH, WRKY, and NAC), and 16 other regulators (mainly including transporter proteins, zinc-finger protein, and others). Our results provide new insights for elucidating the function of anthocyanins in C. japonica petal color expression.